Phenotypic characterization and molecular identification of Malaysian Pseudomonas fuscovaginae isolated from rice plants - Ab Wahab, Mohd Zafri; Sijam, Kamaruzaman; Ismail, Mohd Razi; Hashim, Marzukhi; Mohd Hata, Erneeza; Mohamed Zulperi, Dzarifah (Academic Journals, 2015)
Sheath Brown Rot (SBR) is one of the most important diseases that affect rice plant. The disease cause rots to the sheaths, panicles and leaves of rice plant. The disease also contaminating rice seeds through grain’s discoloration thus leads in reduction of rice production. In this study, 50 bacteria isolates that fluoresced under UV illumination on King’s B Selective (KBS) medium were obtained. Out of 50 isolates, 25 isolates were positive for both Hypersensitivity Reaction (HR) and pathogenicity tests. They also showed positive results for several biochemical reactions such as oxidase, arginine dihydrolase and trehalose utilization tests. Based on the preliminary tests, all isolates have been identified as Pseudomonas fuscovaginae (P. fuscovaginae). The 16S rDNA sequence analysis showed that all the isolates had 97-99% sequence similarities to Pseudomonas fuscovaginae in the GenBank database. This result was also supported by the constructed phylogenetic tree with the Acidivorax avenae outgroup. It was noted that all 25 isolates originated from the same node with the P. fuscovaginae group. The findings on characteristics of P. fuscovaginae in Peninsular Malaysia hopefully can be used in future studies especially on Malaysian P. fuscovaginae biology and their control.